Losing Prospective Entitlement to Unemployment Benefits. Impact on Educational Attainment - Bart Cockx; Koen Declercq; Muriel Dejemeppe (Institute of Labor Economics (IZA), 2022)
Providing income support to unemployed education-leavers reduces the returns to investments in education because it makes the consequences of unemployment less severe. We evaluate a two-part policy reform in Belgium to study whether conditioning the prospective entitlement to unemployment benefits for education-leavers on age or schooling attainment can affect educational achievements. The results show that the prospect of financial loss in case of unemployment can significantly raise degree completion and reduce dropout in higher education, but not in high school. We argue that the higher prevalence of behavioral biases among lower educated and younger students could explain these contrasting findings.
Keywords: H52; I21; I26; I28; J08; J18; J24; J65; J68; 330; unemployment insurance; conditionality; degree completion; school dropout; behavioral biases